(untitled) (Journal of Economic Research & Business Administration, 2016)
The smooth functioning of any modern economic system, an important role belongs to the state. State throughout its history, along with the tasks of maintaining order, the rule of law, the organization of national defense, to perform certain functions in the economy. In modern conditions, any State shall regulate the national economy, with varying degrees of state intervention in the economy. Slowing the growth of Kazakhstan’s economy in 2015 was largely due to a significant reduction in domestic demand against the backdrop of the weakening of the national currency. At the same time, despite the deterioration in external conditions, the adjustment of the tenge exchange rate has supported economic growth due to the increase in net exports.